The Movement of Podillia Clergy for Ukrainization of the Orthodox Church (Second Half of the Nineteenth – Early of the Twentieth Century) - Koshel, Oleksii (Український історичний журнал, 2020)
In the middle of the nineteenth century, the Orthodox clergy of Podillia eparchy of the Russian Orthodox Church began the process of Ukrainization of church life, translation of sermons and, especially, Holy Scripture into the native language, and the revival of national traditions in the church sphere. Two periods of such activity have been considered in the article: the attempts to translate Holy Scripture, prayers and sermons into Ukrainian in the middle of the nineteenth century and in 1905–1912, on the example of the national-spiritual selfless devotion of Archpriest Vasyl Hrechulevych, Archbishop Parfenii (Pamfil Levytskyi) and other figures. Little-known facts of the attempts to translate Holy Scripture in 1862 by Volodymyr Rodnevych, a graduate of Podillia Theological Seminary, have been elucidated. The aim is to analyze and generalize the process of spreading in the second half of the nineteenth – early twentieth centuries among the Orthodox clergy of Ukrainian eparchies of the Russian Orthodox Church (ROC), the movement, aimed at Ukrainization of church life, translation of Holy Scripture and sermons into Ukrainian. During the study, the methods of comparison, logical analysis, synthesis and generalization were used. The scientific novelty of the article is that due to the introduction of little-known archival materials into scientific circulation, in particular from the Russian State Historical Archive, the role of the Orthodox Podillia clergy in Ukrainization of the church in the second half of the 19th – early 20th centuries has been considered in detail. It is affirmed that their activities were closely connected with the personalities of the Ukrainian national revival. In particular, the cooperation with M.Kostomarov and P.Kulish on publishing sermons of V.Hrechulevych in Ukrainian, and also joint work on editing the translation of Holy Scripture into Ukrainian of the commission headed by Bishop Parfenii together with O.Levytskyi, S.Yefremov, B.Hrinchenko, P.Zhytetskyi have been considered. Little-known facts about the attempt to translate Holy Scripture by V.Rodnevych in 1862 have been highlighted, as well as other evidence of conducting divine services in Ukrainian. It has been stated in the conclusions that the process of Ukrainization of church life was initiated by patriotic representatives of Podillia clergy in the middle of the nineteenth century and was spread to other Ukrainian eparchies of the ROC. The activity of the clergy and its close cooperation with the personalities of the national and cultural educational movement initiated and deepened the process of Ukrainization of church life, which was one of the grounds for founding the Ukrainian Autocephalous Orthodox Church in 1919. The publication of Holy Scripture in the Ukrainian language was a significant achievement of the Ukrainian nation-formation and strengthened the movement for Ukrainization of church, in particular the introduction of teaching Ukrainian history and literature in theological seminaries.